Preparation of new GO-based slide ring hydrogel through a convenient one-pot approach as methylene blue absorbent. (1st May 2018) - Soleimani, Khadijeh; Dadkhah Tehrani, Abbas; Adeli, Mohsen
Graphical abstract: Highlights: New GO-based slide ring hydrogel prepared via convenient one-pot process. Obtained SRHG modified by grafting of poly acrylamide on its surface. Resulting Hydrogel effectively absorbed methylene blue in a short time. Results showed that the adsorption kinetics followed a pseudo-second-order model. Abstract: Slide ring hydrogels (SRHG) with supramolecular structures are a new class of hydrogels that contrary to the traditional hydrogels comprise dynamic cross-linking points. Herein, we reported on the fabrication of a new slide ring hydrogel through a very convenient one-pot approach. In this regard, isocyanate functionalized GO was synthesized and used as a stopper as well as cross-linker in the presence of a polypseudorotaxane of cyclodextrin threaded on poly(ethylene glycol) (PR). The surface of the resulting SRHG modified via graft polymerization with polyacrylamide (PAAm) and its application as a new type of absorbent for wastewater treatment was studied. Due to its porous structure and its high content of surface functional groups, the synthesized hydrogel was able to efficiently remove cationic dye methylene blue (MB) from wastewater in a short time. The maximum adsorption capacity of the resulting hydrogel was 92.3 mg/g which exhibited an almost 100% increment as compared to that of untreated GO. The adsorption mechanism of MB was also investigated. The kinetic data, obtained at the optimum pH 7, were fitted well with the pseudo-second-order model. Results from degradation and recycling experiments toward MB showed that the SRHG was stable and reusable.